Effects of early-life environmental stress on risk-taking tendency of adolescents in rural areas of southwestern China - Wu, Jing; Wu, Qiaobing (Frontiers in Psychiatry, 2024)
IntroductionAdolescence is a critical developmental phase characterized by increased risk-taking behaviors, which are not inherently maladaptive. According to life history theory, individuals raised in harsh and unpredictable environments are more likely to adopt faster life history strategies, favoring immediate rewards over long-term benefits. Yet, limited empirical research explore the psychological mechanism about how early-life environmental stresses influence adolescents’ risk-taking. In rural China, left-behind children face economic and social vulnerabilities due to parental migration to urban areas for employment. This study’s first goal was to identify the specific elements of early-life environmental stresses that impact adolescents’ risk-taking tendencies from a developmental evolutionary perspective. The second goal was to construct and test a synthesized model of how objective and subjective environmental stresses influence adolescents’ risk-taking.MethodsA total of 610 middle school students in rural China completed questionnaires assessing early-life environmental stresses and risk-taking tendencies. The sample included 318 left-behind adolescents, 120 single-left-behind adolescents with one parent, and 138 non-left-behind adolescents. Structural equation modeling tested the hypothesized model, examining direct and indirect effects of environmental stresses on risk-taking.ResultsObjective early-life environmental stresses, such as low socioeconomic status (SES), high mortality cues, and high mobility cues, predicted faster life history strategies, marked by shorter future orientation and increased risk-taking tendencies. Subjective perceptions of environmental unpredictability and parental warmth mediated the influence of SES on risk-taking. Biological sensitivity moderated mortality cues’ influence on perceived parental warmth. Sense of control failed to mediate the relationship between early-life stresses and risk-taking. Left-behind adolescents experienced more mobility and mortality cues, perceived greater unpredictability, and reported less parental warmth than their peers. Despite no significant difference in overall risk-taking, left-behind adolescents exhibited higher health/safety risk-taking tendencies.DiscussionThis study provides a comprehensive model linking early-life environmental stresses to adolescents’ risk-taking, integrating objective and subjective measures of stress. The findings offer insights into mechanisms driving risk-taking tendencies. Also, it have significant implications for developing interventions aimed at mitigating the adverse effects of early-life stress on adolescent development, particularly for left-behind children in rural China.